(untitled) (Filološke studije, 2019)
Subject of interest of our paper is the Iindo-Europian men goodnes and it’s parallels with mens goodnes represented in the Macedonian traditional wavings. By comperative analysis, this iconographic type is comprered with the analogue image of the coptic textiles dated from the 10- 12th century A.D., with the 1400-year old image on a silver plate belonging to the group of the so-called Luristabs bronzes and the aerlu Slavic artefact dated from the 7th century A.D. - the plates of a cult caracter foud in Velestino in Thessaly. The close ralations of their theonims Z’rvan-Zvarun-Zvarog-Svarog as well as the etimological components of their names point to the close ralations between Z’rvan and Svarog, as a mythical solar goodnes. Those images have close anlogoges with the Slavic folk embroideries dated from the 19th and the beginning of the 20th centuries.